Human-derived fecal virome transplantation (FVT) reshapes the murine gut microbiota and virome, enhancing glucose regulation - Melany Cervantes-Echeverría; Marco Antonio Jimenez-Rico; Rubiceli Manzo; Abigail Hernández-Reyna; Fernanda Cornejo-Granados; Shirley Bikel; Victor Gonzalez; Juan Manuel Hurtado Ramírez; Filiberto Sánchez-López; Jonathan Salazar-León; Gustavo Pedraza-Alva; Leonor Perez-Martinez; et al. (PLoS ONE, 2025)
The gut microbiome, comprising bacteria, viruses, archaea, fungi, and protists, plays a crucial role in regulating host metabolism and health. This study explored the effects of fecal virome transplantation (FVT) from healthy human donors on metabolic syndrome (MetS) in a diet-induced obesity (DIO) mouse model, without diet change. Mice received a single oral dose of human-derived virus-like particles (VLPs) and continued on a high-fat diet (HFD) for 17 weeks. Despite persistent dietary stress, FVT significantly improved glucose tolerance. Longitudinal profiling by virome shotgun metagenomics and bacterial 16S rRNA sequencing revealed marked, durable shifts in both viral and bacterial community composition. Notable bacterial changes included a decrease in Akkermansia muciniphila and Peptococcaceae and increases in Allobaculum and Coprococcus ; A. muciniphila positively correlated with glucose levels and negatively correlated with body weight. Together, these results suggests that human-derived virome can durably reshape gut microbial ecology and improve glucose metabolism in mice with obesity, even without dietary modification, offering a novel avenue for developing phage-based therapies. This proof-of-concept study provides foundational observations for using human-derived VLPs for FVT in standard laboratory mouse models, and provides a foundation for elucidating bacteria-phage interactions and their role in host metabolic health.